Sosialisasi Pemahaman Insentif Pajak pada UMKM dan Pemaksimalannya pada Masa Pandemi di Denpasar Bali - Tiara Kusuma Dewi; Kukuh Rian Setiawan; I Ketut Yudana Adi (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
This service activity aims to provide socialization about student understanding of the importance of using tax incentives and how to maximize them during the Covid-19 pandemic. This activity is also useful as a stimulus for students who own or accompany Micro, Small and Medium Enterprises to get their rights in the form of tax incentives during the Covid-19 pandemic. This activity consists of 3 stages starting from the first stage in the form of observing problems encountered by UMKM, then discussing them using the focus group discussion method, the second stage, namely online socialization using the Google Meet platform, and the third stage of practicing student understanding in cases that have been prepared previously. Based on the activities that have been carried out, the results show that 71% of students involved in this program are able to understand and be able to apply it to a case, it is hoped that after this activity students can provide real work results in the form of assistance to UMKM in their respective regions in order to have a positive impact for economic development during the pandemic.